E-Commerce Design by Older Adults: The Selection and Placement of Web Objects on Shopping Sites - Osman, Rozianawaty; Hwang, Faustina (Frontiers in Computer Science, 2021)
This paper offers insights, gathered from co-design activities with older adults, on the design of e-commerce websites. Twenty older adults (aged 52 to 75) took part in a paper-based design activity in which they were presented with a web browser window, cutouts of a selection of web objects (e.g. product images, ‘add to cart’ buttons) in a range of designs, and office stationery for making annotations, and asked to select and place web objects onto the browser window to express their design ideas for two types of shopping experience: purchasing a grocery item that is inexpensive and typically purchased in multiples (carrots), and purchasing an assistive technology item which is considered expensive and normally purchased as a one-off (wheelchair). Objects selected frequently by the older adults for inclusion in both types of e-commerce websites included product images, price, and an ‘add to cart’ button. Some objects were selected for inclusion depending on the type of website - quantity selection was selected for the cheap, multiple purchase item, whereas descriptions, reviews and shipping/return information were deemed important only for the expensive, single-item purchase. Regarding the relative placement of the ‘add to cart’ button, participants most often placed the button close to the quantity selection and/or the price. Furthermore, participants expressed that having these three elements presented within a visually-distinctive ‘buy box’ would be beneficial. This study offers insight into which website elements are deemed important to older adults for e-commerce websites and how the elements should be arranged, and the results also indicate that some design requirements may differ between different types of shopping experience. The findings can potentially benefit designers, developers and industries to more fully grasp the potential of usable online shopping applications.